Prahara Digital Labor dalam Bingkai Penafsiran Logika Waktu Pendek dan Kapitalisme Luwes - Putranto, Hendar (Universitas Brawijaya, 2024)
When the COVID-19 pandemic gradually subsided, digital disruption was considered a game changer for today's work, such as work from home (WFH). The prevalence of digital disruption in contemporary work has triggered the birth of a digital labor class, which broadly impacts intra- and inter-organizational communication, especially in dealing with work-related risks in an increasingly insecure labor market. In a macro context like this, digital labor within neoliberal higher education institutions became an interesting phenomenon, especially given the worsening conditions of intellectual workers and changes in academic behavior and practices. A recent study showed many practices violating academic integrity in Indonesian higher education institutions, such as plagiarism, data fabrication, improper claims of authorship, contract-cheating, and other violations of professional codes of ethics. To address these problems, the author employed a critical method of the political economy of communication and the sociology of work to analyze 'short-time logic' as an operational mechanism in flexible capitalism, commoditizing workers' time by blurring the boundaries between productive and leisure time and turning the illusion of worker autonomy into a 'sustained contestation.' The 'short time logic' of flexible capitalism deformed intellectual workers in higher education in Indonesia into digital labor because they were constantly conditioned to produce intellectual products with highly competitive metrics but lacking reflection and meaningfulness, which sharpened the gaps in competency-based inequalities and created a new hierarchy of social classes in higher education.